Pengaruh Model Guided Note Taking terhadap Hasil Belajar Biologi Siswa Kelas XI SMA Negeri 6 Kota Lubuklinggau - Dian Samitra; Yuni Krisnawati; Novita Malasari (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2018)
The purpose of this study was to determine the effect of the Guided Note Taking learning model on the learning outcomes of biology students in class XI of SMA N 6 Lubuklinggau in the academic year 2017/2018. The design applied in this research is pretest-posttest control group design. The research sample was obtained using a random sampling technique. Namely students of class XI.IPA.4 as a control class and class XI.IPA.3 as an experimental class. To obtain student learning outcomes after treatment, a multiple choice test is used with a total of 26 items. The results of student learning data obtained through tests were analyzed using t-tests. The results of the t-test analysis showed that t-count> t-table (4.01> 1.68), it could be interpreted that the average value of the experimental class was greater than the average value of the control class. It can be concluded that the Guided Note Taking learning model influences the biology learning outcomes of Grade XI students of SMA Negeri 6 Lubuklinggau. Suggestions for improving student biology learning outcomes, teachers should innovate learning and apply active learning models. Keywords: learning outcomes, biology, guided note taking, models